From Heroic Retribution to Civilized Violence: Victorian Images of War and the Making of General Gordon - Michael Anton Budd (Cahiers Victoriens et Edouardiens)
This article considers the emergence of Charles George Gordon (1833–1885) as new type of Christian technological hero in the context of Victorian representations and discussions concerning war. Gordon’s example demonstrates the role of technology in relation to the heroic in three ways: by the atavistic desire for the pure categories of the past, which seemed to have been swept aside by capital and new industry; by virtue of the role of print, image and communication technologies to spread the knowledge of the new hero’s exploits, and by the fact that the hero, in military and other contexts, was increasingly a technologist. My aim is to investigate Gordon’s own ambivalence about the technological militarized society he came to represent in the context of the crisis narratives proceeding from the Crimea and the Sepoy Mutiny to the debacle at Khartoum and its aftermath.